2020
DOI: 10.1002/14651858.cd011748.pub3
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 monoclonal antibodies for the primary and secondary prevention of cardiovascular disease

Abstract: BackgroundDespite the availability of effective drug therapies that reduce low-density lipoprotein (LDL)-cholesterol (LDL-C), cardiovascular disease (CVD) remains an important cause of mortality and morbidity. Therefore, additional LDL-C reduction may be warranted, especially for patients who are unresponsive to, or unable to take, existing LDL-C-reducing therapies. By inhibiting the proprotein convertase subtilisin/kexin type 9 (PCSK9) enzyme, monoclonal antibodies (PCSK9 inhibitors) may further reduce LDL-C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
2
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 94 publications
3
61
2
9
Order By: Relevance
“…Updated analysis shows that there is evidence for treating patients with PCSK9i, who are not eligible for other drugs or who cannot reduce LDL-C on traditional therapies. However, the evidence base of PCSK9i against other active treatments is weaker 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Updated analysis shows that there is evidence for treating patients with PCSK9i, who are not eligible for other drugs or who cannot reduce LDL-C on traditional therapies. However, the evidence base of PCSK9i against other active treatments is weaker 25 .…”
Section: Introductionmentioning
confidence: 99%
“…These results agreed with the analysis of secondary prevention in our network meta-analysis. Whether PCSK9i can reduce mortality, however, is controversial ( Schmidt et al, 2020 ). Our findings showed that PCSK9i added to background high-intensity statins was associated with a reduced risk of all-cause mortality and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Lp(a) should now be considered a therapeutic target, especially after ACS [82]. There was a tremendous advantage when comparing alirocumab or evolocumab with placebo or ezetimibe plus a statin in another trial; however, the benefit difference between the two groups was not significant when comparing the two groups utilizing the combination of ezetimibe and statin [83].…”
Section: Treatment Of High Lipoprotein (A)mentioning
confidence: 99%